2014
DOI: 10.1186/1477-7525-12-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors as predictors of quality of life in chronic portuguese patients

Abstract: BackgroundChronic illnesses are diseases of long duration and generally of slow progression. They cause significant quality of life impairment. The aim of this study was to analyse psychosocial predictors of quality of life and of subjective well-being in chronic Portuguese patients.MethodsChronic disease patients (n = 774) were recruited from central Portuguese Hospitals. Participants completed self-reported questionnaires assessing socio-demographic, clinical, psychosocial and outcome variables: quality of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 33 publications
(45 reference statements)
4
20
1
1
Order By: Relevance
“…34 On the other hand, patients with a positive affect, social support, adequate treatment adherence, and spirituality felt better regarding their disease conditions and, consequently, had a better quality of life. 35 Pain beliefs are important predictors of treatment outcome and should be considered in the management of TMD patients. 8 A prospective study showed that two risk factors for elevated TMD incidence were greater numbers of comorbid pain conditions and a greater Case-control N = 23 TMD.…”
Section: Discussionmentioning
confidence: 99%
“…34 On the other hand, patients with a positive affect, social support, adequate treatment adherence, and spirituality felt better regarding their disease conditions and, consequently, had a better quality of life. 35 Pain beliefs are important predictors of treatment outcome and should be considered in the management of TMD patients. 8 A prospective study showed that two risk factors for elevated TMD incidence were greater numbers of comorbid pain conditions and a greater Case-control N = 23 TMD.…”
Section: Discussionmentioning
confidence: 99%
“…Coping strategies: The Coping Strategies Inventory [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] was used for this evaluation, which consists of 19 items scored on four levels of intensity. The items are grouped into five factors: Factor 1: expression of negative emotions (items 1, 7, 9, 13, 18 and 19) -behavioral excesses and risk behaviors that allow the individual to spare himself/ herself of feelings of guilt, resentment or doubts, deal with situations of anxiety and depression and make contact with others to achieve assistance or maintain emotional activation.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…The degree of optimism is a characteristic of the personality of each individual and an aspect that assists in seeking better results 14,15 . Recent investigations have shown that sufficient optimism results in more effective coping strategies, as individuals tend to act in a more proactive manner to deal directly with the source of the problem 16,17 . Among caregivers of dependent individuals, a higher degree of optimism is related to a lower level of care-related burden 18 .…”
mentioning
confidence: 99%
“…Estos resultados coinciden con los de Vilhena et al (30) en cuanto a la importancia del bienestar emocional en la calidad de vida percibida.…”
Section: Enfermería Globalunclassified